Interactive Effects of Organizational Structure and Team Work Quality on Project Success in Project Based Non Profit Organizations - Hayat, Khunsa; Hafeez, Maryam; Bilal, Kanwal; Shabbir, Malik Shahzad (iRASD Journal of Management, 2022)
The main aim of the research paper is to explore the interactive usefulness of organizational hierarchy or structure as well as teamwork quality regarding organizational structure from (Khyber Pakhtunkhwa) a province of Pakistan. The data is collected through questionnaires from the employees working in the project-based organizations in non-profit sectors of Pakistan. The data is analyzed through Statistical Package for the Social Sciences (SPSS). This research shows that there is a highly considerable positive association between the type of structure an organization chose to work in and project success. The teamwork quality has a 28.5% impact on the project success on the dependent variable. The moderator and dependent variable are highly relatable with a considerable amount of values, as per results statistics.